Molecular prevalence and associated risk factors of Anaplasma ovis in Pakistani sheep - Naeem, Muhammad; Amaro-Estrada, Itzel; Taqadus, Asia; Swelum, Ayman A.; Alqhtani, Abdulmohsen H.; Asif, Muhammad; Sajid, Muhammad; Khan, Asmat Ullah; Tariq, Aliza; Anjum, Summaya; Khan, Adil; Iqbal, Furhan (Frontiers in Veterinary Science, 2023)
Background Majority of Pakistani population lives in rural areas and raising animals, especially the small ruminants, is their primary source of income. Anaplasma ovis is known to infect small ruminants globally and causing significant economic losses to livestock owners, however prevalence of Anaplasma ovis has been least investigated from Pakistan despite having a huge sheep population. Methods The present study was conducted from June 2021 till December 2021 to report the PCR based prevalence of Anaplasma ovis in the blood samples of sheep (n = 239) that were collected from District Dera Ghazi Khan in Pakistan. Results Out of 239 samples, 30 (12.5%) amplified a 347 bp fragment specific for the msp4 gene of Anaplasma ovis. Represented partial msp4 gene sequences were confirmed by Sanger sequencing and deposited to GenBank (OP620757-59). None of the studied epidemiological factors (age, sex, breed, size of herd, dogs with herd, and composition of herd) showed an association (P > 0.05) with the Anaplasma ovis infection in enrolled sheep. Analysis of the amplified partial mSP4 sequence of Anaplasma ovis revealed that this gene is highly conserved as all three sequences were identical and phylogenetically resembled with the msp4 sequences amplified from small ruminants in China, Kenya, and Germany, Turkey, Portugal, Tunisia and India. In conclusion, for the first time, we are reporting a moderate prevalence of Anaplasma ovis prevalence in Pakistani sheep and this data will help in developing the integrated control policies against this newly reported tick-borne disease that is infecting our sheep breeds.